PENGARUH MOTIVASI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT RIA INDAH MANDIRI CIBINONG - Yasnimar Ilyas; Dheby Aprilia Widystuti (Economicus : Jurnal Ekonomi dan Manajemen, 2021)
This study aims to determine the effect of the independent variables (motivation, discipline, and work environment) on the dependent variable (employee performance) at PT Ria Indah Mandiri Cibinong. The results showed that: In the partial test (t-test) it shows that the variables of motivation, discipline and work environment have a significant influence on the performance of employees at PT Ria Indah Mandiri Cibinong, because the value of t count is greater than t table, with a value of t count. respectively 3,204, 3,113 and 4,931 (>) greater than t table 1,667. Simultaneously, motivation, discipline, and work environment have a significant effect on employee performance at PT Ria Indah Mandiri Cibinong, because the value of f count 64.476 is greater than f table 2.16. From the variables of motivation, discipline, and work environment, the variable that more dominantly affects employee performance is the work environment variable (X3), because the t value is greater than the other variables, which is 4,931. In the test results the coefficient of determination (adjusted R²) which is obtained is 0.726, this means that 72.6% of employee performance variables are affected quite highly by the variables of motivation, discipline, and work environment. While the remaining 27.4% is influenced by other factors that are not discussed in this study.